The development’s phases of educational sciences as academic disciplin in Hungary in first half of the 20th century (Foro de Educacion, 2017)
A number of historical anthologies and monographs have been published recently that give priority to the social approach in the history of science of the educational sciences – using Stichweh’s concept of discipline – as discipline formation and discipline development. The study to date indicates that four phases in the academic discipline development of the educational sciences in Hungary can be distinguished. In the first phase we find the institutional formation of pedagogy, as it was then understood, as a disciplinary field. This development proceeded most rapidly in the last third of the nineteenth century. It took on two overlapping forms, following the general institutionalization of teacher education. On the one hand, broad-based theory formation regarding educational practice took place, reaching its peak in Herbartianism. On the other hand, university courses were introduced and academic chairs created, often closely tied to philosophy, that were dedicated to pedagogy and represented the academic foundations of the discipline. The second phase, which is the focus of the present contribution continued into the twentieth century. In this period an educational movement arose that centered on the empirical paradigms of research in the social sciences. But the various lines of the movement (reform pedagogy, experimental pedagogy, child study) did not always succeed at becoming established at the universities. The third phase is the phase of lasting institutionalization of the educational sciences, which in most places began already in the first half of the twentieth century. Here the German «Geisteswissenschaft» played a role. After the 2nd World War was Hungary included in the sphere of influence of the Soviet Union and began the fourth phase of development of the educational sciences in Hungary. Educational science was most highly affected among social sciences by the political power shifts oft the Stalinism.